(untitled) (AYUSHDHARA, 2024)
Ayurveda is the science of life. Agni is the unique and one of the most important concepts of Ayurveda. There are 13 different forms of Agni described in the Ayurvedic classics; like Jatharagni, Dhatwagni, Bhutagni etc. According to Acharya Charaka Shama and Prakopa states of Doshas always depend on Agni. Aims and Objectives: To study the concept of Agni and Dosha and analyse the concept of Agni and its relationship with Doshas. Materials and Method: This is a review article based on the collection of materials from available sources in Ayurveda like Brihattrayi, Laghutrayi, online articles, online journals etc. Discussion: According to Ayurveda there are three Doshas in the body. These Doshas are the intrinsic factors for Vyadhi Utpatti. The Doshas manifest the diseases or maintain the health on dependent of State of equilibrium and vitiation. As Dosha are the vitiating factors of the body and mind it also affects function of the Agni. Here Agni is responsible for health and Bala of a person. Hence, due to Prakopa of Dosha normal function of Agni gets hamper and can cause many kinds of pathogenesis and can manifest different type of diseases. Conclusion: Shamana and Prakopa of Dosha is depended on Agni. Hence any changes in the status of Dosha cannot be performed without the influence of Agni.